2019
DOI: 10.12700/aph.16.4.2019.4.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Business Enabling Policies, Tax Treatment, Corruption and Political Connections on Business Climate

Abstract: The impact of the institutional environment on the business activity was a subject of several previous studies. However, the ways in which changes in institutions affect business climate have not received proper attention from scholars as of yet. The purpose of this paper is to fill this gap in the literature by examining the relationship between selected formal institutions (business enabling policies and tax treatment) and informal institutions (corruption and political connections) and business climate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…For this reason, the impact assessment of governmental support of SMEs and its comparison among countries is a challenging task. However, similar results with the present paper are found even by prior research (Čadil et al, 2017;Çera, Breckova, et al, 2019). Thus, it seems that entrepreneurs' perception on business climate is not depended on governmental policies aiming business stimulation in general.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For this reason, the impact assessment of governmental support of SMEs and its comparison among countries is a challenging task. However, similar results with the present paper are found even by prior research (Čadil et al, 2017;Çera, Breckova, et al, 2019). Thus, it seems that entrepreneurs' perception on business climate is not depended on governmental policies aiming business stimulation in general.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with prior studies (Bartelsman, Haltiwanger, & Scarpetta, 2010;Brixiová & Égert, 2012;Chowdhury et al, 2019). Therefore, institutional constraints dealing with regulation and legal environment create not a good environment for the business activity leading to unfavourable business climate (Çera, Breckova, Çera, & Rozsa, 2019;Motoyama & Hui, 2015). Evidence showed that the interactives of the above institutional constraints with firm characteristics (sector and firm size) was not significant for predicting business climate.…”
Section: Discussionsupporting
confidence: 90%
“…Given such a positive relationship, it can be concluded that evidence may support the first perspective mentioned in the literature review, which points out that trust positively affects the contracting product. These results are useful for transition countries like Albania, where institutions are relatively weak (Çera, Breckova, et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Communication and shared information between the trading partners is a current topic in particular for an agribusiness context. The role of information on relationship quality is investigated in a developing country like Albania, where institutions are weak and the competitions principles from advance economies are not corrected adopted (Çera, Breckova, Çera, & Rozsa, 2019). Even though there are some studies which informs on the above issues, yet there is a need to better understand the whole picture when it comes to the trading relationship.…”
Section: Discussionmentioning
confidence: 99%